2019
DOI: 10.1016/j.still.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of best management practices for sediment and nutrient loss control using SWAT model

Abstract: The intensive study of an individual watershed is required to develop effective and efficient watershed management plans. Identification of critical erosion-prone areas of the watershed and implementation of best management practices (BMPs) is necessary to control the watershed degradation by reducing the sediment and nutrient losses. The present study evaluates and recommends the BMPs in an agriculture-based Marol watershed (5092 km 2 ) of India, using a hydrologic model, Soil and Water Assessment Tool (SWAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 84 publications
5
59
0
Order By: Relevance
“…On the one hand, the CF, CF+GFB and CF+HFB scenarios were more effective in reducing the organic nitrogen and the sorbed N-NH4 + (Figure 4-22) because these nitrogen forms are fixed to the sediments and their mobilization is associated to soil erosion and sediment yield, while N-NO3 -is more prone to be lost by leaching than via surface runoff (Randall and Mulla, 2001). This effect was also observed by Himanshu et al (2019) who found that contour farming and the installation of filter strips led to higher percentage reductions of organic nitrogen than N-NO3 -. On the other hand, the FM and FM+CR scenarios were effective in reducing the N-NO3 -.…”
Section: Evaluation Of Best Management Practices Scenariossupporting
confidence: 68%
“…On the one hand, the CF, CF+GFB and CF+HFB scenarios were more effective in reducing the organic nitrogen and the sorbed N-NH4 + (Figure 4-22) because these nitrogen forms are fixed to the sediments and their mobilization is associated to soil erosion and sediment yield, while N-NO3 -is more prone to be lost by leaching than via surface runoff (Randall and Mulla, 2001). This effect was also observed by Himanshu et al (2019) who found that contour farming and the installation of filter strips led to higher percentage reductions of organic nitrogen than N-NO3 -. On the other hand, the FM and FM+CR scenarios were effective in reducing the N-NO3 -.…”
Section: Evaluation Of Best Management Practices Scenariossupporting
confidence: 68%
“…Therefore, controlling nutrient and sediment losses from croplands is required to enhance soil, water, and environmental quality (Blanco‐Canqui, ; Martin & Cassel, ). These challenges can be addressed by using and adapting sustainable vegetation management practices such as agroforestry, grass, and biofuel management systems (Himanshu, Pandey, Yadav, & Gupta, ; Jiang, Anderson, Kitchen, Sadler, & Sudduth, ; Kumar, Udawatta, & Anderson, ; Paudel, Udawatta, & Anderson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonpoint-source pollution (NPSP) has become a significant threat to soil and water quality and agricultural production and has received higher global attention from many public agencies and scientists with efforts to find appropriate solutions (Alberts, Wendt, & Burwell, 1985;Conley et al, 2009;Dong, Liu, Wu, Chen, & Guo, 2018;Udawatta, Motavalli, & Garrett, 2004). Rainfall intensity is considered a major dynamic factor of runoff as well as sediment and nutrient (Himanshu, Pandey, Yadav, & Gupta, 2019;Jiang, Anderson, Kitchen, Sadler, & Sudduth, 2007;Kumar, Udawatta, & Anderson, 2010;Paudel, Udawatta, & Anderson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The major challenge for the water managers to fulfil the water requirements of people without imparting any deteriorating effect on the ecological services, provided by the healthy rivers (Bunn et al, ; Yao, Zheng, Tian, Li, & Liu, ). The rapid socioeconomic development and change in climatic conditions over the previous decades have greatly influenced global hydrologic cycle up to the extent of putting a threat to water security, wellness of aquatic ecosystem, and biodiversity of river (Amrit, Mishra, & Pandey, ; Dhami, Himanshu, Pandey, & Gautam, ; Himanshu, Pandey, & Patil, ; Himanshu, Pandey, Yadav, & Gupta, ; Jacobsen, Milner, Brown, & Dangles, ; Van Vliet et al, ; Vörösmarty et al, ). It is very important to understand the role of flow regulation for the sustainability of good hydro‐ecosystems (Turnbull et al, ; Yao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…& Pandey, 2017a; Dhami, Himanshu, Pandey, & Gautam, 2018;Himanshu, Pandey, & Patil, 2018;Himanshu, Pandey, Yadav, & Gupta, 2019;Jacobsen, Milner, Brown, & Dangles, 2012;Van Vliet et al, 2013;Vörösmarty et al, 2010). It is very important to understand the role of flow regulation for the sustainability of good hydro-ecosystems (Turnbull et al, 2012;Yao et al, 2018).…”
mentioning
confidence: 99%